The impact of carbon emission trading policy on regional total factor productivity - Wen, Xin; Meng, Fange (Frontiers in Environmental Science, 2024)
The DEA-Malmquist index approach is used to measure the growth rate of regional total factor productivity. The panel data of 30 regions in China from 2005 to 2020 are used to examine the impact of carbon emission trading policy on regional total factor productivity. The findings demonstrate that, while the carbon emissions trading pilot policy can enhance total factor productivity (TFP), its impact varies across regions. Notably, the policy fosters TFP growth in Beijing and Tianjin but hampers it in Hubei and Guangdong provinces, signifying regional heterogeneity in its effects. These results remain robust even after conducting placebo tests and DID model. Furthermore, the mechanism study reveals that the carbon emissions trading pilot policy affects total factor productivity through pure technical efficiency and scale effects. Given the more stringent environmental regulations brought by the "carbon neutrality" goal, understanding the impact of carbon emissions trading policies on total factor productivity lays the groundwork for establishing a national carbon emissions trading market. This promotes sustainable economic development by helping to achieve a win-win situation between environmental protection and economic growth.